1988
DOI: 10.1093/clinchem/34.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lot-to-lot variability in filter paper on the quantification of thyroxin, thyrotropin, and phenylalanine in dried-blood specimens.

Abstract: We prepared whole-blood pools to contain various concentrations of phenylalanine (Phe), thyroxin (T4), and thyrotropin (TSH) and applied them to six different lots of Schleicher & Schuell Grade 903 filter paper, two of which represented extremes for serum-absorbancy. Individual measured T4 values showed minimal overlap among all pools for each individual filter-paper lot and for all lots combined, but Phe values overlapped considerably among the high-concentration pools within and among lots. Individual TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…We also noticed such color retention in samples stored for prolonged periods only at RT, but not at 4°C or −20°C. The previously published results 11 and results presented here indicate that filter papers used in preparing blood spots may also affect stability and extractability of blood components. Suarez et al 12 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We also noticed such color retention in samples stored for prolonged periods only at RT, but not at 4°C or −20°C. The previously published results 11 and results presented here indicate that filter papers used in preparing blood spots may also affect stability and extractability of blood components. Suarez et al 12 .…”
Section: Discussionsupporting
confidence: 59%
“…Davis and Poholek 1 noted that substantial amounts of red coloration remained on the filter paper indicating incomplete extraction before immunoassay. We also noticed such color retention in samples stored for prolonged periods only at RT, but 11 and results presented here indicate that filter papers used in preparing blood spots may also affect stability and extractability of blood components. Suarez et al 12 studied the effect of three types of filter paper (Whatman BFC 180, Schleicher and Schuell 2992 and 903) on the levels of TSH and TT4 stored for 9 months at 2°C-8°C.…”
Section: Extraction Of Dna and Pcr Reactionssupporting
confidence: 55%
“…9 Other factors include time of collection after birth, season, method of blood spotting as well as temperature, humidity, technical manipulation and time of elution from the filter paper. 7,911 In addition, lot-to-lot differences in the filter papers may also contribute to variability in neonatal testing, although previous studies have suggested that they alone are not sufficient to cause significant errors in neonatal screening. 11…”
Section: Discussionmentioning
confidence: 99%
“…7,911 In addition, lot-to-lot differences in the filter papers may also contribute to variability in neonatal testing, although previous studies have suggested that they alone are not sufficient to cause significant errors in neonatal screening. 11…”
Section: Discussionmentioning
confidence: 99%
“…For the same volume of applied blood, a decreasing area of filter paper is covered with increasing haematocrit in the sample, 2 and this can affect measured analyte concentrations. 3 Batch to batch variation of filter paper contribute to analytical imprecision 4 (though this has been reduced by the development of blood absorption criteria for filter papers by the Clinical and Laboratory Standards Institute in the USA), as does the location of the punch 5 for methods employing non-volumetric blood application, such as newborn screening, in which only a portion of the spot is analysed.…”
Section: Introductionmentioning
confidence: 99%